Investigating the local structure of Ti based MXene materials by temperature dependent X-ray absorption spectroscopy. Issue 4 (6th January 2023) - Olszewski, Wojciech; Marini, Carlo; Kajiyama, Satoshi; Okubo, Masashi; Yamada, Atsuo; Mizokawa, Takashi; Saini, Naurang Lal; Simonelli, Laura
Abstract : The lower Ti–T x disorder for the Ti2 CT x than the Ti3 C2 T x system results in a higher specific capacitance. Abstract : The local structures of Ti based MXene-type electrode materials have been studied by Ti K-edge X-ray absorption fine structure measurements as a function of temperature to obtain direct information on the local bond lengths and their stiffness. In particular, the parent MAX phases Ti2 AlC and Ti3 AlC2 and their etched MXene systems are characterized and their properties compared. We find that selective etching has a substantial effect on the local structural properties of the Ti based MXene materials. It leads to an increase in the interatomic distances, i.e. a decrease in the covalency, and corresponding bond stiffness, that is a likely cause of higher achievable performances. The obtained results underline the importance of the local atomic correlations as limiting factors in the diffusion capacity of ion batteries.